Persepsi Pengguna Media Sosial Desa Ciruluk terhadap Penyebaran Konten Homoseksual pada Aplikasi Tiktok - Iis Isti Rahmawati; Achmad Junaedi Sitika; Debibik Nabilatul Fauziah (AS-SABIQUN, 2022)
Tiktok is a product of communication technology, a place where users can easily participate in sharing, creating content and interact with each other in a virtual world. One of the problems caused by the development of social media is that a lot of negative content has emerged, including homosexual content. This paper discusses the perception of social media users towards the spread of homosexual content on the Tiktok application. The research method used is qualitative, with data sources in the form of direct observations on Tiktok social media, interviews with Tiktok users, and literature studies. The results show that social media users in Ciruluk Village, Kalijati District, Subang Regency, West Java Province have the same perception that homosexual content is very disturbing and detrimental and has a bad impact on Indonesia’s young generation. As for how to respond to homosexual content on the Tiktok application, namely by avoiding watching it, creating positive content, the importance of mentoring from parents so that children avoid negative viewing, and stay away from bad environments and associations.